A Tool to Measure the Attitude of Farmers Toward Conservation Agriculture (Indian Journal of Extension Education, 2023)
When assessing farmers’ predispositions and developing a strategy for extension work in the region, the attitude of farmers toward conservation agriculture is a crucial consideration. The purpose of this study was to develop a valid and reliable instrument for assessing farmers’ attitudes toward conservation agriculture. The scale product method is used to construct the scale. It is a hybrid of the Likert and Thurstone techniques. The study was conducted in March 2022. On a 5-point scale, 65 judges evaluated 25 statements. Finally, 18 statements including 14 positive statements and 4 negative statements were chosen to build a scale that would assess the attitude of farmers towards conservation agriculture. The scale was found reliable, with the reliability coefficient (r) (Guttman split-half Coefficient and Spearman-Brown Coefficient Equal Length) determined to be 0.917. The scale’s validity was evaluated using expert judgement. Employing the scale in research will aid in knowing farmers’ attitudes about conservation agriculture.